The study of customer satisfaction on retail store (Watsons) in Jerantut Pahang / Nurul Nabila Baharuddin - Baharuddin, Nurul Nabila
Customer satisfaction is a promoting term that measures how products or services supplied by an organization meet or surpass a customer's desire. Customer satisfaction is essential since it gives advertisers and entrepreneurs with a metric that they can use to manage and enhance their organizations (Ross Beard, 2014). One of the fundamentally important drivers of organizational success is that entrepreneur must take the needs and wants of their customers into account (Singh, 2006). Satisfaction in this senses, could mean that a supermarket has just scarcely met the customer’s expectations, not exceeded nor disappointed those expectations. The advantages of taking the customer’s response beyond satisfaction at this level by exceeding expectations, is a competitive strategy many retailers aspire to achieve. Satisfaction is a consumer’s postpurchase evaluation of the overall service experience. According to Menonand Dube, it is an affective reaction in which the consumer’s needs, desires and expectations during the course of the service experience have been met or exceeded (Lovelock, 2001). Supermarket retailers continue to adapt to changing consumer demands, industry issues and regulations affecting their businesses. Some grocers are expanding their business, others are narrowing to specialty formats, and some seem to be doing both.